Lock, stock and two smoking barrels [videorecording (Blu-Ray)] - Hughes, David, 1960-; Murphy, John, 1965 March 4- (Universal Studios Home Entertainment, 2009)
A collection of law-dodging characters in London are brought together by coincidence when a streetwise young man loses half-a-million pounds in a card game. He has a week to get together the money or face losing some fingers. Desperate, he and his friends decide to rip off a gang who are planning to rip off a bunch of ganja farmers. Simple. Except the drug dealers want their money back, as do the thieves, and now there are three sets of criminals after their blood.